Κεχαριτωμένη en Lc 1,28 Étude exégétique et théologique - La Potterie, Ignace de (Biblica, 1987)
In an earlier article (Bib 68 [1987] 357-382), we undertook a philological study of the verb charitoô as applied to Mary in Luke 1,28. The conclusion was that kecharitômenè describes the transformation caused in Mary by grace. The present article is an exegetical and theological study of the same verse in three parts: 1) an analysis of the only parallel text in the NT, echaritôsen hèmas in Eph 1,6; 2) the meaning given to kecharitômenè in Tradition, especially since the Byzantine and medieval period; 3) a detailed study of kecharitômenè in its immediate context, beginning with the double parallelism found in its structure (vv. 28 and 30; vv. 28 and 34). The results show that kecharitômenè describes not only the grace of purification received by Mary, but more especially "the grace of virginity" (St. Bemard), in preparation for her virginal motherhood at the Incamation. In the conclusion, it is asked whether a careful study of this gospel verse (on Mary and on grace) might not be a good basis for discussion in order to further ecumenical dialogue.